Church, state and social science in Ireland : Knowledge institutions and the rebalancing of power, 1937-73 - Murray, Peter, 1952-; Feeney, Maria (Book collections on Project MUSE., 2017)
The immense power the Catholic Church once wielded in Ireland has considerably diminished over the last 50 years. During the same period the Irish state has pursued new economic and social development goals by wooing foreign investors and throwing the state's lot in with an ever-widening European integration project. How a less powerful church and a more assertive state related to one another during the key third quarter of the 20th century is the subject of this book. Drawing on newly available material, it looks at how social science, which had been a church monopoly, was taken over and bent to new purposes by politicians and civil servants.